Generation of Anti‐Mastitis Gene‐Edited Dairy Goats with Enhancing Lysozyme Expression by Inflammatory Regulatory Sequence using ISDra2‐TnpB System - Rui Feng; Jianglin Zhao; Qian Zhang; Zhenliang Zhu; Junyu Zhang; Chengyuan Liu; Xiaoman Zheng; Fan Wang; Jie Su; Xianghai Ma; Xiaoyu Mi; Lin Guo; et al. (Advanced Science)
Abstract Gene‐editing technology has become a transformative tool for the precise manipulation of biological genomes and holds great significance in the field of animal disease‐resistant breeding. Mastitis, a prevalent disease in animal husbandry, imposes a substantial economic burden on the global dairy industry. In this study, a regulatory sequence gene editing breeding strategy for the successful creation of a gene‐edited dairy (GED) goats with enhanced mastitis resistance using the ISDra2‐TnpB system and dairy goats as the model animal is proposed. This included the targeted integration of an innate inflammatory regulatory sequence (IRS) into the promoter region of the lysozyme (LYZ) gene. Upon Escherichia Coli (E. coli) mammary gland infection, GED goats exhibited increased LYZ expression, showing robust anti‐mastitis capabilities, mitigating PANoptosis activation, and alleviating blood‐milk‐barrier (BMB) damage. Notably, LYZ is highly expressed only in E. coli infection. This study marks the advent of anti‐mastitis gene‐edited animals with exogenous‐free gene expression and demonstrates the feasibility of the gene‐editing strategy proposed in this study. In addition, it provides a novel gene‐editing blueprint for developing disease‐resistant strains, focusing on disease specificity and biosafety while providing a research basis for the widespread application of the ISDra2‐TnpB system.